Guessing personality from a brief sample of behaviour - Wu, Wenjie (2015)
Mentalising as a process for explaining and predicting behavior relates to inferring mental states and traits of others. Previous research of mentalising has focused too heavily on mental states and insufficiently on personality traits. Given this context, the current thesis aimed to explore the phenomenon of forming first impressions of personality based on a brief sample of behavior.